Identifying mental health nursing research priorities: A Delphi study - Wynaden, Dianne; Heslop, Karen; Al Omari, O.; Nelson, D.; Osmond, B.; Taylor, M.; Gee, T. (eContent Management, 2014)
Engaging in research and using evidence based practice are essential for mental health nurses to provide quality nursing care to consumers and families. This paper reports on a Delphi study that identified the top ten mental health nursing research priorities at one area health service in Australia servicing a population of 840,000 people. Initially 390 research questions were identified by nurses and these were then reduced to 56 broader questions. Finally, the top ten questions were ranked in order of importance. The priority questions were clinically and professionally focused and included research into the delivery and organisation of mental health services and the need to design and evaluate new practice paradigms for nurses in the primary care setting. The mental health knowledge and skill set of graduates from Australian comprehensive nursing programs along with improved recruitment and retention of graduates in mental health were also identified priority areas for research.